2016
DOI: 10.1038/sj.bdj.2016.913
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study: assessing the efficacy and social acceptability of using dental hygienist-therapists as front-line clinicians

Abstract: Background The oral health of the adult population has been improving in the United Kingdom decade upon decade. Over half of dental service activity in the National Health Service (NHS) is limited to a check-up without any further treatment. This raises a question as to whether check-ups could be provided by dental hygienist-therapists, rather than general dental practitioners. The aim of this study was to assess the feasibility of a definitive trial to evaluate the costs and effects of using dental hygienist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…However, in a descriptive study which examined the attitudes of new patients to mid-level providers working independently to dentists, they found 98 percent of responding patients were satisfied with their mid-level provider care, and 80 percent attended a dental appointment within the next 12 months (43). This concurs with other studies, which found that patients who have a high degree of satisfaction with their experience with midlevel providers (11,39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in a descriptive study which examined the attitudes of new patients to mid-level providers working independently to dentists, they found 98 percent of responding patients were satisfied with their mid-level provider care, and 80 percent attended a dental appointment within the next 12 months (43). This concurs with other studies, which found that patients who have a high degree of satisfaction with their experience with midlevel providers (11,39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 92%
“…The trial should be designed to capture all possible health gains from receiving a dental check‐up such as the detection of periodontal disease or changes in the patient's education, motivation, and behavior in oral self‐care and follow patients or extrapolate the health and cost effects into the long term. A feasibility study exploring this has recently been completed in the UK .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing population health suggests that demand on primary care for general dental practitioner examinations with little or no further treatment will increase with time. 1 However, improvements in global dental health also means that an elderly population retaining dentition for longer 2 is leading to a parallel population with complex treatment needs. 3 The mix of skills in the dental workforce has been extensively debated for many years.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Improving population health suggests that dental examinations with little or no further treatment need will increase with time. 5 Improvements in oral health and reductions in the prevalence of dental caries and periodontal disease 3 mean that while children and adults may require minimal intervention. However, an increasing population of older patients will retain their dentition for longer 6 and for a number of decades to come, will present with complex treatment needs.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, the majority of dentistry practiced is not complex; much of the work of general dental practitioners (GDPs) relates to routine examinations and simple maintenance . Improving population health suggests that dental examinations with little or no further treatment need will increase with time . Improvements in oral health and reductions in the prevalence of dental caries and periodontal disease mean that while children and adults may require minimal intervention.…”
Section: Introductionmentioning
confidence: 99%